STAGES OF THE ESTABLISHMENT AND DEVELOPMENT OF YOUTH ENTREPRENEURSHIP AMONG EDUCATION GAINERS (Innovative professional education, 2023)
Small business has always been the leading sector of the market economy since it is mobile and dynamic. And as of today and in the post-war period, this sector will play, if not the main, then one of the key roles in the development of the national economy. Since the foundation of the development of the state's economy is labor resources, and every year there is an increase in the number of young people who want to get professional education, it is appropriate, in my opinion, to activate and more widely introduce the appropriate knowledge and skills in entrepreneurial activity among those seeking education. The formation of entrepreneurial competence among schoolchildren will make it possible to consciously choose one's own path to professional success, will teach how to analyze and make effective decisions not only in the economic sphere, but also in various life situations, because entrepreneurial activity is multi-vector.
Keywords: youth entrepreneurship, vocational schools, education applicants, bases of enterprise activity, entrepreneurial competence